Analgesic effect of intravenous dexamethasone after volar plate surgery for distal radius fracture with brachial plexus block anaesthesia: a prospective, double‐blind randomised clinical trial*. (30th May 2020) - Holmberg, A.; Hassellund, S. S.; Drægni, T.; Nordby, A.; Ottesen, F. S.; Gulestøl, A.; Ræder, J.
Summary: Rebound pain after brachial plexus block resolution and development of long‐lasting pain are problems associated with volar plate fixation for distal radius fractures. The aim of this double‐blind study was to evaluate the effect of a single prophylactic intravenous dose of dexamethasone in this setting. The primary endpoint was highest pain score during the first 24 hours after surgery. We included 51 adults of ASA physical status 1–2 due to undergo planned acute fixation of the radius. All received premedication with oral paracetamol and etoricoxib, and a pre‐operative brachial plexus block with ropivacaine. Patients were randomly allocated into two groups: a dexamethasone group receiving 16 mg dexamethasone intravenously at start of surgery and a control group receiving 4 ml saline. After surgery, all patients received fixed doses of paracetamol, etoricoxib and oxycodone, with further oxycodone added as needed in the first 48 hours. Pain, analgesic consumption and daily function were registered at predefined times up to 1 year after surgery. Median (IQR [range]) worst pain score in the first 24 hours, as assessed by verbal numeric rating scale (0–10), was 4 (2‐6 [0–7]) in the dexamethasone group compared with 8 (5–8 [2–10]) in the placebo group (p < 0.001). Average pain score, 2 (1–4 [0–5]) vs. 5 (3–6 [0–8]), p = 0.001 and rescue oxycodone consumption, 5 (0‐10 [0‐35]) mg vs. 10 (5‐15 [0‐50]) mg, p = 0.037), respectively, were both significantly lower in the dexamethasone group compared with control from 8 to 24 hours. Brachial plexus block duration was 69% longer in the dexamethasone group, 21.5 (19.1‐23.4 [12.9‐24.1]) hours vs. 12.7 (11.9‐15.3 [7.4‐26.6]) hours, p < 0.001. Two patients (9%) in the dexamethasone group compared with 12 (50%) in the placebo group experienced worst pain scores of 8‐10 during the first 36 hours (p = 0.002). At 3 and 7 days postoperatively, there were no significant differences between groups for pain scores or opioid consumption. At 6 months, 27 patients (57%) reported pain at the site of surgery, with significantly higher average pain score (p = 0.024) in the placebo group. At 1 year, two patients in the dexamethasone group reported pain compared with 10 in the placebo group (p = 0.015), and worst pain score was significantly higher in the placebo group (p = 0.018). We conclude that intravenous dexamethasone improves early postoperative analgesia and may also improve clinical outcomes after 6 and 12 months.